The Politics of Europe - Bonefeld, W. author. aut Link
VIII, 200 p.
Keywords: Assessments of the politics of European integration in general, and monetary union in particular, are many. In fact, the study of the European Union has become an academic growth industry. This book contributes to the debate a specific theoretical focus and practical perspective. The volume provides a critique of the political economy of European integration and its unique focus and scholarly analysis make it an indispensable contribution to a renewal of the Marxist critique of European integration.